(untitled) (Research, Society and Development, 2020)
The present work aims to evaluate the influence of the incorporation of the solution obtained with hibiscus, sucrose and sodium chloride in the osmotic dehydration process and the study of Air fryer drying kinetics in the physical and physicochemical characteristics. The eggplant was cut into cubes measuring 1.0 × 1.0 × 1.0 cm and underwent osmotic dehydration in a hypertonic solution infused with hibiscus for 30 minutes at 25 ± 2 ° C after this step. the percentage of water loss (PA) and solids gain (GS) was determined. The study of drying kinetics was performed in an Air fryer household equipment at temperatures of 70, 80 and 90 ° C and the air velocity of the equipment itself (not adjustable) and empirical mathematical models were adjusted to the experimental data. Fresh eggplant cubes and after drying at the temperatures indicated above were characterized as to the following parameters: pH, total titratable acidity (ATT), water content, total solids, total soluble solids (SST), ratio (SST/ATT) and color (L *, a *, b *, C * and h °). The osmotic dehydration process caused a reduction in the initial water content of the fruit and a solids gain of 16.34%. Regarding the drying kinetics, the Page model presented the highest coefficients of determination (R2) and the lowest values of chi-square function at all temperatures analyzed; The increase in drying temperature provided greater color difference, indicating efficiency in the process of impregnating the eggplant hibiscus infusion. Therefore, the temperature of 90 ° C is the most suitable for drying eggplant cubes, as it presented the lowest water content and good physical and physicochemical characteristics.